Synthetic domestic wastewater sludge as electron donor in the reduction of sulphate and treatment of acid mine drainage - Van den Berg, Francis (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.